Sustained multiplicity in everyday cholesterol reduction: repertoires and practices in talk about 'healthy living'. Issue 2 (21st January 2014) - Will, Catherine M.; Weiner, Kate
Abstract This article is concerned with talk about and the practices of healthy living in relation to cholesterol reduction. It draws on qualitative interviews with 89 people who are current or former users of either cholesterol‐lowering functional foods or statins for cardiovascular risk reduction. Focusing on data about everyday activities including food preparation, shopping and exercise, we illustrate four repertoires that feature in talk about cholesterol reduction (health, pleasure, sociality and pragmatism). Using Gilbert and Mulkay's notion of a 'reconciliation device', we suggest ways in which apparently contradictory repertoires are combined (for example, through talk about moderation) or kept apart. We suggest that, in contrast to the interactiveness of the repertoires of health and pleasure, a pragmatic repertoire concerning food provisioning, storage and cooking as well as the realities of exercise, appears distinct from talk about health and is relatively inert. Finally we consider the implications of these discursive patterns for daily practices. Our data suggest there is little emphasis on coherence in people's practices and illustrate the significance of temporal, spatial and social distribution in allowing people to pursue different priorities in their everyday lives. Rather than the calculated trade‐offs of earlier medical sociology we draw on Mol to foreground the possibility of sustained multiplicity in daily practices.